Histochemical Testing and Microscopic Structure of Leea indica (Burm.f.) Merr. (Memaye) as a Medicinal Plant of the Besemah Tribe for Anti-infective and Degenerative Purposes in Lahat, South Sumatra - Nina Tanzerina; Muti Elyani; Nita Aminasih; Endri Junaidi; Harmida Harmida (Eduvest - Journal of Universal Studies, 2026)
Leea indica (Burm.f.) Merr. (Memaye) is traditionally used by the Besemah Tribe in Lahat, South Sumatra, as a medicinal plant to treat infectious and degenerative diseases, including hepatitis, liver disorders, and warts. The utilization of this plant as an herbal remedy requires comprehensive information on its microscopic characteristics and secondary metabolite content. This research aimed to determine the classes of secondary metabolite compounds with anti-infective and anti-degenerative potential and their distribution in the vegetative organs of L. indica through histochemical testing, as well as to identify specific diagnostic fragments from microscopic observation of simplicia powder and stem maceration preparations. Histochemical tests were performed on fresh cross-sections of leaves, stems, and roots using specific reagents: Wagner's reagent for alkaloids (reddish-brown positive), 10% NaOH for flavonoids (yellow), 5% copper acetate for terpenoids (yellow to brownish), 10% FeCl₃ for phenols (greenish-black), and Lugol's iodine for tannins (black or purple). Microscopic observations were conducted on chloral hydrate-mounted simplicia powder and safranin-stained maceration preparations. Results showed that alkaloids, terpenoids, tannins, and phenols were distributed in all vegetative organs, while flavonoids were detected exclusively in leaves. Diagnostic fragments, including various crystal types (raphide, druse, rosette), trichomes (glandular, non-glandular, scale, and septate), and vascular elements (tracheae, tracheids, fibers, and xylem parenchyma), were identified across leaves, stems, and roots. Notably, scale trichomes and septate trichomes with basal sacs serve as specific diagnostic fragments for L. indica, providing reliable authentication markers for quality control in medicinal applications and future research.